Causal relationship between gut microbiota, blood metabolites and autism spectrum disorder: a Mendelian randomization study - Jigan Wang; Hui-Hong Dou; Qiong-You Liang (Royal Society Open Science)
This study explored the causal relationships between gut microbiota, blood metabolites and autism spectrum disorder (ASD) in children and assessed whether metabolites mediate the relationship between microbiota and ASD. Using Mendelian randomization (MR), causal links between gut microbiota, blood metabolites and ASD were analysed, alongside reverse MR to examine reverse causality. A two-step MR mediation analysis was used to assess metabolite mediation. The study identified 15 gut microbiota types significantly associated with ASD, with Marinilabiliaceae showing the strongest positive link (odds ratio (OR) = 5.206, 95% confidence interval (CI) = 1.2783–21.2017, p = 0.0213) and Poseidoniaceae the strongest negative association (OR = 0.1466, 95% CI = 0.0306–0.7035, p = 0.0164). Among 52 blood metabolites, 4-methylcatechol sulphate was positively associated with ASD risk (OR = 1.6776, 95% CI = 1.0482–2.6849, p = 0.0311), while the glucose-to-maltose ratio showed a negative relationship (OR = 0.6358). No significant reverse causal effects of ASD on microbiota or metabolites were found. Nine metabolites mediated the relationship between microbiota and ASD, with 1-methyl-5-imidazoleacetate showing the strongest negative mediation effect (mediating effect = −0.0862, mediation proportion = 12.30%). This study reveals complex causal pathways involving microbiota and metabolites in ASD, suggesting metabolites may mediate the microbiota–ASD relationship, offering insights into ASD mechanisms and potential interventions.